As e^(itheta)=costheta+isinthetaeiθ=cosθ+isinθ, we have
e^((pi)/4i)=cos((pi)/4)+isin((pi)/4)=1/sqrt2+i1/sqrt2eπ4i=cos(π4)+isin(π4)=1√2+i1√2
e^((35pi)/4i)=cos((35pi)/4)+isin((35pi)/4)e35π4i=cos(35π4)+isin(35π4)
= cos(8pi+(3pi)/4)+isin(8pi+(3pi)/4)cos(8π+3π4)+isin(8π+3π4)
= cos((3pi)/4)+isin((3pi)/4)cos(3π4)+isin(3π4)
= cos(pi-(pi)/4)+isin(pi-pi/4)cos(π−π4)+isin(π−π4)
= -cos((pi)/4)+isin(pi/4)−cos(π4)+isin(π4)
= -1/sqrt2+i1/sqrt2−1√2+i1√2
Hence e^((pi)/4i)-e^((35pi)/4i)=(1/sqrt2+i1/sqrt2)-(-1/sqrt2+i1/sqrt2)eπ4i−e35π4i=(1√2+i1√2)−(−1√2+i1√2)
= (1/sqrt2+1/sqrt2)+i(1/sqrt2-1/sqrt2)(1√2+1√2)+i(1√2−1√2)
= 2/sqrt2+0=sqrt22√2+0=√2